PELATIHAN PENGGUNAAN MEDIA E-LEARNING BERBASIS SCHOOLOGY PADA GURU SD IT MUTIARA CENDEKIA LUBUKLINGGAU - Lucy Asri Purwasi; Nur Fitriyana; As Elly s; Denny Alfian (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
The purpose of this activity is to increase the knowledge and competence of teachers in implementing schoology-based E-learning learning, and 2) through this activity to motivate teachers to implement schoology-based E-learning learning in order to optimize ICT-based learning. The basic education unit in Lubuklinggau City consists of public and private elementary schools, one of which is the Mutiara Cendekia IT Elementary School, which is a partner in this service activity. IT Cendekia Mutiara Elementary School Lubuklinggau is a private elementary school that has complete facilities, including a computer laboratory. The training participants were 32 teachers of the Mutiara Cendekia IT Elementary School. The training is carried out for 3 days with a minimum time of 32 hours. The methods for implementing the activities are: 1) the preparation and observation stage, 2) the socialization stage, 3) the implementation stage, and 4) the evaluation stage. The results of the achievement of this activity were 1) the number of participants was considered enthusiastic, followed by 32 teachers, more than the targeted number of participants, and 2) the teacher's response to the schoology-based e-learning media showed interest and response was very good with the percentage of response questionnaires reaching 85%.